Comparative analysis of olfactory sensory neurons in two Ips species reveals conserved and species-specific olfactory adaptations - Shewale, Mayuri Kashinath; Bláha, Jaromír; Synek, Jiří; Schebeck, Martin; Andersson, Martin N.; Kandasamy, Dineshkumar; Jirošová, Anna (Frontiers in Forests and Global Change, 2025)
IntroductionBark beetles spend most of their lives under the bark of trees, with some species being economically significant pests that cause widespread tree mortality. Their behavior is primarily driven by olfactory signals, with aggregation pheromones playing a prominent role alongside volatiles from hosts, non-host trees, and associated microbes. These signals are detected by olfactory sensory neurons (OSNs) housed in hair-like sensilla on the antennae. In this study, we focused on two Ips species with distinct host preferences: Ips acuminatus, which infests pine species, and Ips cembrae, which primarily attacks European larch. To better understand species-specific adaptations and shared olfactory mechanisms, we compared their olfactory responses with those of Ips typographus, a major pest of Norway spruce. By investigating the frequency, specificity, and antennal distribution of various OSN classes, we aimed to uncover both conserved and different olfactory mechanisms across Ips species with different host associations.MethodsWe conducted single sensillum recordings (SSR) to examine OSN responses in the antennal olfactory sensilla of I. acuminatus and I. cembrae. The responses were compared to existing data from I. typographus to identify potential species-specific adaptations and conserved olfactory mechanisms. A panel of 57 ecologically relevant odorants was tested, comprising interspecific and intraspecific pheromones, along with compounds associated with host- and non-host trees, as well as symbiotic fungi.Results and discussionBased on their response profiles, we identified nineteen OSN classes in both I. acuminatus and I. cembrae. A few selected OSN classes were further analyzed using dose–response tests to assess their specificity and sensitivity. Three OSN classes in I. acuminatus and four in I. cembrae were specific to host-related compounds. Two OSN classes responded to non-host volatiles, while one OSN class exhibited strong responses to microbial volatiles in both species. Several OSN classes specific to pheromone compounds, non-host, and microbial volatiles showed similar response profiles in both I. acuminatus and I. cembrae as well as in OSN classes previously reported in I. typographus, potentially reflecting close phylogenetic relationships and shared ecological traits among these species.